PSVII-12 Investigating the influence of copper supplementation on copper homeostatic genes in bovine liver. (30th November 2020) - Tillquist, Nicole M; Thorndyke, Meghan P; Thomas, Tyler A; Coleman, Stephen J; Engle, Terry E
Abstract: The objective of this experiment was to investigate the influence of copper (Cu) supplementation on Cu homeostatic genes in bovine liver. Liver samples were obtained from multiparous cows (n = 3 cows per treatment) from a previous experiment. Treatments consisted of: 1) no supplemental Cu (-Cu; total diet contained 7.0 mg Cu/kg DM) and 2) 3 mg Cu/kg DM (+Cu; total diet contained 10.0 mg Cu/kg DM). Cows were fed their respective diets for 420 d. Liver samples were harvested immediately upon slaughter, rinsed with phosphate-buffered saline solution, diced into small pieces, and placed into RNAlater and frozen at -80°C. Total RNA was extracted from all samples, and quantitative RT-PCR was used to determine the abundance of transcripts for proteins involved in Cu homeostasis in liver tissue. The target transcripts were: ALDH2, APOA1, ATOX1, ATP7A, ATP7B, BHMT, BLVRB, CA2, CCS, COX17, CTR1, ELN, GAPDH, GLUD1, GSS, LOXL1, PDIA3, SOD1, SOD3. The relative abundance of APOA1, ATOX1, ATP7B, BLVRB, CTR1, GLUD1, LOXL1, and SOD3 mRNA was greater (P < 0.05) in cows receiving supplemental Cu when compared to cattle not receiving supplemental Cu. These data indicate possible differences in Cu homeostasis in the liver based on Cu supplementation. Further investigation is warranted to determine if a difference in the relative abundance of identified transcripts are related to differences in associated protein production and function.